The potential impacts of circadian rhythm disturbances on male fertility - Li, Tao; Bai, Yunjin; Jiang, Yiting; Jiang, Kehua; Tian, Ye; Gu, Jiang; Sun, Fa (Frontiers in Endocrinology, 2022)
A circadian rhythm is an internalized timing system that synchronizes the cellular, behavioral, and physiological processes of organisms to the Earth’s rotation. Because all physiological activities occur at a specific time, circadian rhythm disturbances can lead to various pathological disorders and diseases. Growing evidence has shown that the circadian clock is tightly connected to male fertility, and circadian perturbations contribute to infertility. The night shiftwork, insufficient sleep, and poor sleep quality are common causes of circadian disturbances, and many studies have reported that they impair sperm quality and increase the risk of male infertility. However, research on the impacts of light, body temperature, and circadian/circannual rhythms is relatively lacking, although some correlations have been demonstrated. Moreover, as the index of sperm quality was diverse and study designs were non-uniform, the conclusions were temporarily inconsistent and underlying mechanisms remain unclear. A better understanding of whether and how circadian disturbances regulate male fertility will be meaningful, as more scientific work schedules and rational lifestyles might help improve infertility.